The mechanical property of palm oil fuel ash as partial cement replacement in cement brick - Mohd Taufiq, Hasabulah (2015)
Both palm oil fuel industry and cement industry are causing native impact to the enviroment.The amount of land needed for the disposal of the waste can become increasing. Palm oil fuel ash are the waste products from the local palm oil industry that cause environmental pollution when they are discarded at the same time, cement are costly and production cause negative impact to the enviroment. Issue on the depletion of natural cement has lead towards the utilization of Palm Oil Fuel Ash (POFA) as cement replacement in the cement replacement production. Furthermore, the incorporation of POFA as partial cement replacement material in concrete production also helps us to reduce the cost of concrete production and able to curb environmental pollution problem. The objective of the study are to determine the effect of palm oil fuel ash (POFA) as partial cement replacement content on the compressive strength and moisture absorption of (POFA) cement brick. The impact of compressive test and water absorption test of cement brick containing palm oil fuel ash as partial cement replacement material has been investigated Concrete specimens with various percentage of palm oil fuel ash (POFA) as partial cement replacement material were water cured for 28 days before subjected towards compressive strength test and water absorption test. Findings shows that cement brick containing 20% of POFA demonstrate highest compressive strength compared to the other specimens. Inclusion of 20% POFA has lead to densification of cement brick internal structure making the concrete denser and exhibit lowest water absorption of all mixes.